Creativity and television drama: a corpus-based multimodal analysis of pattern-reforming creativity in House M.D. Issue 2 (August 2019) - Law, Locky
Abstract : Carter's (2004) theory of creativity in everyday common talk is by far the most influential in the field. He hypothesises that linguistic creativity can be categorised into pattern-forming and pattern-reforming creativity. Television drama, despite its global popularity, receives little attention from the field of linguistics. This paper aims to explore the 'common ground' in television drama dialogue and linguistic creativity through deciphering how pattern-reforming creativity is realised through screenplay, telecinemato-graphy and acting as meaning-making strategies. Using dialogues from the TV medical dramedy House M.D., a corpus was created to facilitate the extraction of pattern-reforming creativity such as neologisms, portmanteaus and slang words. The extracted data was then analysed using a corpus linguistic approach to multimodal discourse analysis. The analysis reveals a strong association of pattern-reforming creativity production with actor's facial performance realised interpersonally by certain types of telecinematic resources, such as visual framing, camera angle, camera movement and proxemics. This research is a pioneering effort in linking up linguistic creativity with multimodality and is a positive driving force towards research in teledramatic discourse.